EXPERIMENTAL AND NUMERICAL INVESTIGATIONS OF CONTINUOUS COMPOSITE GIRDERS REINFORCED WITH CFRP - unknown (2020)
Continuous composite steel-concrete girders composed of cast-in-place concrete slab and steel girders are widely used in bridges and buildings. In design, the concrete slab at the negative moment region is ignored for composite action because of tensile stress, and the steel girder is assumed to either act alone or compositely with the longitudinal slab reinforcement. The inactiveness of slab in composite action at negative moment regions diminishes the full composite action of the girders, resulting in its reduced strength and stiffness. This research presents experimental and numerical investigations on the use of Carbon Fiber Reinforced Polymer (CFRP) to maintain the composite action at the negative moment region of continuous composite girders. This is achieved by bonding CFRP sheets to the top of concrete slab at the negative moment region. A total of six two-span continuous composite girders were tested. The girders were designed to have full composite action between the concrete slab and steel girder. The experimental results confirmed effectiveness of CFRP sheets to maintain the composite action at negative moment region under service load. The use of CFRP also improved strength and stiffness of the continuous composite girders. Three-dimensional Finite Element (FE) model of continuous composite girder was developed using commercial software ABAQUS and validated with the experimental results. The developed model was used to investigate the proper thickness and length of CFRP sheets to achieve the full plastic capacity of composite girders and avoid premature failure of CFRP and epoxy adhesive. The model results were used to obtain the required number of shear connectors to develop full composite action between steel beam and concrete slab at negative moment zone. Experimental and numerical results were used to develop simplified design approach to compute the required thickness of CFRP sheets to strengthen continuous composite girder.